Pyridine nitrogen-rich nitrogen-doped graphene-loaded nano-iron composite material as well as preparation method and application thereof

By dispersing nano-iron particles on nitrogen-doped graphene, the problem of nano-iron easy oxidation and agglomeration in groundwater repair is solved, and the efficient preparation of composite materials and excellent chlorinated hydrocarbon degradation effect is achieved.

CN119869449APending Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311380254.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Nanovalent iron is easily oxidized in groundwater repair applications to form a passivation layer, reducing activity, and easily agglomerated, affecting transmission efficiency. The existing improved methods are complex, costly and are not suitable for large-scale commercial preparation.

Method used

Using pyridine nitrogen-rich nitrogen-doped graphene as a support, the nano-iron particles are dispersed to form a composite material by liquid reduction with an iron source in an alkaline reduction solvent. This method is simple and reduces engineering costs.

Benefits of technology

It improves the dispersion and stability of nano-iron particles, enhances the mass transfer efficiency, and has excellent activation and removal effects on the degradation of chlorinated hydrocarbons.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869449A_ABST
    Figure CN119869449A_ABST
Patent Text Reader

Abstract

The invention relates to a pyridine-nitrogen-rich nitrogen-doped graphene-loaded nano-iron composite material and a preparation method and application thereof.The method comprises the following steps that 1, graphene oxide, a nitrogen source and a solvent are subjected to first mixing, and a first mixture is obtained; performing pyrolysis on the first mixture in an inert atmosphere to obtain nitrogen-doped reduced graphene; and (2) carrying out contact reaction on the nitrogen-doped graphene, an iron source, a reducing reagent and water, and sequentially carrying out cleaning, magnetic separation and first freeze drying on a reaction product. The method is simple and convenient, and the engineering cost can be effectively reduced; the composite material prepared by the method disclosed by the invention has good dispersity and stability, is high in mediation mass transfer efficiency, and has excellent activation and removal effects on degradation of chlorinated hydrocarbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of groundwater in-situ remediation materials, and in particular, to a pyridinic nitrogen-rich nitrogen-doped graphene-loaded nano-iron composite material and a preparation method and application thereof. Background Art

[0002] With the advancement of the construction of groundwater pollution prevention and control pilot areas, the management of groundwater environmental governance has been continuously strengthened. Under the requirements of reducing environmental disturbances and protecting the ecosystem to the greatest extent, in-situ remediation technology has become a key area of ​​research and application for groundwater pollution remediation due to its advantages of small engineering workload and low cost. At present, there are many types of in-situ remediation technologies, some of which have been applied in actual projects, while others are in the pilot or laboratory research stage.

[0003] Nano zero-valent iron (nZVI) has a small particle size and a large specific surface area, which gives it a certain adsorption capacity and good reaction activity. In 1994, Professor Gillham first used metal iron filings in an actual groundwater remediation project. Since then, the research on the reduction of halogenated organic pollutants and heavy metals by zero-valent iron has become increasingly popular in site environmental remediation. Nano zero-valent iron (nZVI) is conducive to in-situ injection into the underground to form a reaction zone due to its advantages such as small particle size, high reduction potential and active chemical properties, so it can achieve green and low-disturbance remediation of contaminated groundwater. However, nano iron is prone to oxidation to form a passivation layer, which reduces its activity, and is prone to agglomeration, thereby reducing the transmission efficiency. It still faces challenges in actual site remediation applications. To address these problems, researchers have used surfactants, polymers or carrier loading methods to improve the agglomeration problem of nZVI; and transition metal deposition or coating methods have been used to alleviate its passivation effect.

[0004] Carbon materials have been widely studied due to their potential applications in military, environmental protection, energy storage, medical and other fields. Carbon materials loaded with nZVI have both anti-agglomeration and anti-passivation properties. Among them, reduced graphene has become the most promising carbon material carrier due to its excellent physical and chemical properties. In order to expand its scope of application, researchers have adopted many strategies, including regulating the physical and chemical properties of carbon materials. For example, the electrochemical reduction method is used to pass an electric current between the substrate and the counter electrode to achieve the oxidation stripping process of the carbon material; the carbon material is doped with heteroatoms by increasing the pressure; or a sacrificial template method is used to use a large molecular weight polymer as a precursor to strip non-essential elements to form a functionalized carbon material with multiple functional groups. These methods are relatively complex, costly, and require harsh experimental conditions, which are not conducive to large-scale commercial preparation, and cannot meet the material requirements for in-situ groundwater remediation. Summary of the invention

[0005] The purpose of the present disclosure is to provide a composite material of pyridinic nitrogen-rich nitrogen-doped graphene loaded with nano-iron and a preparation method and application thereof. The method disclosed in the present disclosure is simple and can effectively reduce engineering costs.

[0006] In order to achieve the above object, the present disclosure provides a method for preparing a composite material of pyridinic nitrogen-rich nitrogen-doped graphene loaded with nano-iron, the method comprising the following steps:

[0007] (1) first mixing graphene oxide, a nitrogen source and a solvent to obtain a first mixture; placing the first mixture in an inert atmosphere for pyrolysis to obtain nitrogen-doped graphene;

[0008] (2) contacting and reacting the nitrogen-doped graphene, the iron source, the reducing agent and water, and sequentially washing, magnetically separating and freeze-drying the reaction product.

[0009] Optionally, in step (1), the graphene oxide is mixed with the solvent to form a graphene oxide suspension, and then the graphene oxide suspension is mixed with the nitrogen source to obtain the first mixture; the concentration of the graphene oxide suspension is 2 to 20 g / L, preferably 6 to 15 g / L; the solvent includes water and / or ethanol; the nitrogen source is a nitrogen-containing compound selected from one or more of nitrates, ammonia water, urea, biomass and hydrazine hydrate; preferably one or more of urea, ammonia water and hydrazine hydrate; more preferably urea;

[0010] The mass ratio of the nitrogen source to the graphene oxide is 1 to 3:1.

[0011] Optionally, in step (1), the pyrolysis conditions include: a heating rate of 5 to 15°C / min, a pyrolysis temperature of 300 to 900°C, and a pyrolysis time of 1 to 5 hours; preferably, the heating rate is 7 to 12°C / min, the pyrolysis temperature is 500 to 700°C, and the pyrolysis time is 2 to 4 hours.

[0012] Optionally, in step (1), the conditions of the first mixing include: the first mixing is carried out under stirring, the stirring speed is 110 to 260 rpm, preferably 180 to 210 rpm; the temperature of the first mixing is below 40°C, preferably 20 to 40°C; the time of the first mixing is 4 to 20 hours, preferably 6 to 10 hours; the first mixture is in a sludge-like state, and the water content is 70% to 98%.

[0013] Optionally, in step (2), the iron source is a ferric salt and / or a ferrous salt; the iron source is selected from one or more of FeCl3, FeCl2 and FeSO4·7H2O; preferably a ferrous salt, more preferably FeSO4·7H2O;

[0014] The mass ratio of the iron source to the nitrogen-doped graphene is 4.9 to 44.7:1, preferably 4.9 to 14.9:1;

[0015] The reducing agent comprises a reducing agent and an alkaline substance, the reducing agent is selected from one or more of KBH4, NaBH4 and hydrazine hydrate, and the alkaline substance is selected from one or more of sodium hydroxide and potassium hydroxide; preferably, the reducing agent comprises NaBH4 and sodium hydroxide;

[0016] The mass ratio of the iron source to the reducing agent is 1.46-3.65:1, preferably 1.46-2.43:1; in the reducing agent, the molar ratio of the reducing agent to the alkaline substance is 1-20:1, preferably 2.5-13.5:1.

[0017] Optionally, step (2) includes: performing a second mixing of the nitrogen-doped graphene, the iron source and water to obtain a second mixture; performing a third mixing of the reducing agent and water to obtain a reducing solvent; dropping the reducing solvent into the second mixture to carry out the contact reaction; the dropping speed is 0.5 to 1.5 mL / min, preferably 0.7 to 1.2 mL / min; the pH of the reducing solvent is 12.8 to 13.5.

[0018] Optionally, in step (2), the magnetic separator obtained by the magnetic separation is subjected to the first freeze-drying; the conditions of the first freeze-drying include: temperature below -50°C, preferably -57 to -73°C, time 15 to 24 hours, preferably 18 to 22 hours.

[0019] Optionally, the graphene oxide is prepared by adopting a modified Hummers method.

[0020] A second aspect of the present disclosure provides a composite material prepared by the method described in the first aspect of the present disclosure.

[0021] The third aspect of the present disclosure provides a composite material of nitrogen-doped graphene loaded with nano-iron rich in pyridinic nitrogen, the composite material comprising nitrogen-doped graphene and nano-iron particles loaded on the nitrogen-doped graphene;

[0022] Based on the total number of atoms of the composite material, the atomic percentage of iron in the composite material is 0.2-70%, and the atomic percentage of nitrogen is 0.4-10%, wherein the pyridine nitrogen content accounts for 30-60% of the nitrogen content.

[0023] Optionally, the nano iron particles are of a core-shell structure and the shell thickness is 1 to 4 nm.

[0024] Optionally, the BET specific surface area of ​​the nitrogen-doped graphene is 200 to 500 m2 / g; the average particle size of the nano iron particles is 50-60nm; the average pore size of the composite material is 3.5-4.0nm.

[0025] The fourth aspect of the present disclosure provides use of the composite material described in the second aspect or the third aspect of the present disclosure in the remediation of groundwater contaminated by chlorinated hydrocarbons, wherein the mass ratio of the composite material to the chlorinated hydrocarbon is 1 to 5:1.

[0026] Through the above technical scheme, the present invention pyrolyzes graphene oxide and a nitrogen source to obtain pyridine-rich nitrogen-doped reduced graphene, and then performs liquid phase reduction with an iron source in an alkaline reducing solvent to disperse nano iron particles on the nitrogen-doped reduced graphene. The method disclosed in the present invention is simple and can effectively reduce engineering costs; the composite material prepared by the method disclosed in the present invention has good dispersibility and stability, and has high mediated mass transfer efficiency, and has excellent activation and removal effects on the degradation of chlorinated hydrocarbons.

[0027] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0029] Figure 1 This is a scanning electron microscope image of the composite material of Example 1 of the present disclosure.

[0030] Figure 2 1 and 2 are high-resolution transmission electron microscope images of the composite material of Example 1 of the present disclosure, wherein (a) is a high-resolution transmission electron microscope image at a low magnification, and (b) is a high-resolution transmission electron microscope image at a high magnification.

[0031] Figure 3 X-ray photoelectron spectroscopy (XPS) graphs of the nitrogen-doped graphene material (a) and the nitrogen-doped graphene-loaded nano-iron composite material (b) prepared in Example 1 of the present disclosure.

[0032] Figure 4 (a) N2 adsorption / desorption isotherm and (b) pore size distribution diagram of the composite material prepared in Example 1 of the present disclosure.

[0033] Figure 5 This is a curve diagram of the thermal stability of the composite material of Example 1 of the present disclosure.

[0034] Figure 6 This is the removal curve of tetrachloroethylene by the nitrogen-doped graphene-loaded nano-iron composite material prepared in Example 1, Example 2 and Example 3 of the present disclosure. DETAILED DESCRIPTION

[0035] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0036] The first aspect of the present disclosure provides a method for preparing a composite material of nitrogen-doped graphene loaded with nano-iron and rich in pyridinic nitrogen, the method comprising the following steps:

[0037] (1) first mixing graphene oxide, a nitrogen source and a solvent to obtain a first mixture; placing the first mixture in an inert atmosphere for pyrolysis to obtain nitrogen-doped graphene;

[0038] (2) contacting and reacting the nitrogen-doped graphene, the iron source, the reducing agent and water, and sequentially washing, magnetically separating and freeze-drying the reaction product.

[0039] The method disclosed in the present invention uses reduced graphene as a carrier, improves the free carrier density of reduced graphene by doping defects with N atoms, further improves the electron transfer ability of graphene sheets, changes the spin density and charge distribution of adjacent carbon atoms, and thus introduces more active sites. The surface of the nitrogen-doped graphene disclosed in the present invention has a large number of functional groups and active sites, which can promote the uniform dispersion and smaller size distribution of nano-iron particles on its surface; in addition, the close interaction between the nano-iron particles and the nitrogen-doped graphene further improves the structural stability and reaction activity of the composite material.

[0040] Secondly, the nitrogen doping of the composite material disclosed in the present invention contains a relatively high content of pyridinic nitrogen; the pyridinic nitrogen-rich doped graphene anchors the nano-iron material, and integrates the three-functional synergistic effect of "enrichment-reduction mediation-activation of C-Cl bonds" to achieve efficient dechlorination: the huge specific surface area, high basal hydrophobicity and π electron conjugation of the nitrogen-doped graphene (N-rGO) substrate are utilized to enhance the adsorption capacity of chlorinated hydrocarbons; the efficient mediation ability of pyridinic nitrogen-doped reduced graphene is utilized to transfer the reduction active sites to the entire composite surface, effectively alleviating the surface passivation of the nano-iron particles (nZVI) and improving the mass transfer efficiency; nitrogen doping changes the spin density and charge distribution of adjacent carbon atoms, introduces more active sites, and strengthens the adsorption and breaking of C-Cl bonds, thereby reducing the difficulty of dechlorination and improving the thoroughness of dechlorination.

[0041] Furthermore, the composite material prepared by the method disclosed in the present invention has better stability. Nitrogen-doped graphene is used as a skeleton material, which effectively improves the dispersibility of the composite material in water. The suspended slurry is easier to be injected into the ground in situ to form an in situ reaction zone. The composite material is negatively charged in the solution and has good dispersibility, making it easier to migrate in the aquifer. The composite material disclosed in the present invention maintains magnetism after the reaction, which is convenient for separation. In addition, the method of the present invention is relatively simple and effectively reduces engineering costs.

[0042] According to one embodiment of the present disclosure, in step (1), the graphene oxide is mixed with the solvent to form a graphene oxide suspension, and then the graphene oxide suspension is mixed with the nitrogen source to obtain the first mixture; the concentration of the graphene oxide suspension is 2 to 20 g / L, preferably 6 to 15 g / L; the solvent includes water and / or ethanol; the nitrogen source is a nitrogen-containing compound selected from one or more of nitrates, ammonia water, urea, biomass and hydrazine hydrate; preferably one or more of urea, ammonia water and hydrazine hydrate; further preferably urea; the mass ratio of the nitrogen source to the graphene oxide is 1 to 3:1. In a further embodiment, the solvent is a mixed solution of ethanol and water, and in the mixed solution, the ethanol concentration is 30% to 95%, preferably 50% to 60%. The above embodiment is conducive to obtaining a composite material with a better structure, avoiding affecting the dispersibility and stability of the composite material, and further avoiding affecting the recovery of the composite material.

[0043] According to an embodiment of the present disclosure, in step (1), the pyrolysis includes placing the first mixture in a quartz boat and performing the pyrolysis in a tube furnace; the conditions of the pyrolysis include: a heating rate of 5 to 15°C / min, a pyrolysis temperature of 300 to 900°C, and a pyrolysis time of 1 to 5 hours; preferably, a heating rate of 7 to 12°C / min, a pyrolysis temperature of 500 to 700°C, and a pyrolysis time of 2 to 4 hours; the inert atmosphere includes one or more of nitrogen, helium, and argon. The above-mentioned embodiment is conducive to better nitrogen doping, obtaining nitrogen-doped graphene with richer pyridine nitrogen form, and further preparing a composite material with better structure.

[0044] According to an embodiment of the present disclosure, in step (1), the conditions of the first mixing include: the first mixing is carried out under stirring, the stirring speed is 110-260 rpm, preferably 180-210 rpm; the temperature of the first mixing is below 40°C, preferably 20-40°C; the time of the first mixing is 4-20 hours, preferably 6-10 hours; the first mixture is sludge-like, and the water content is 70%-98%. The above embodiment is conducive to obtaining a composite material with a better structure and obtaining a composite material with good dispersibility and stability.

[0045] According to one embodiment of the present disclosure, an inert atmosphere is used as a protective gas before, during and after the pyrolysis process, and the inert atmosphere includes one or more of nitrogen, helium and argon, preferably nitrogen. In one embodiment, the pyrolysis device is evacuated before pyrolysis, and the evacuation operation is a conventional operation in the art, for example, including introducing 300 to 500 sccm of nitrogen into the tubular furnace for evacuation, and the ventilation time is 10 to 20 minutes.

[0046] According to an embodiment of the present disclosure, in step (2), the iron source is an iron salt and / or a ferrous salt; the iron source is selected from one or more of FeCl3, FeCl2 and FeSO4·7H2O; preferably a ferrous salt, more preferably FeSO4·7H2O; the mass ratio of the iron source to the nitrogen-doped graphene is 4.9 to 44.7:1, preferably 4.9 to 14.9:1. The above embodiment is conducive to obtaining a composite material with a better structure and obtaining a composite material with good dispersibility and stability.

[0047] According to an embodiment of the present disclosure, the reducing agent includes a reducing agent and an alkaline substance, the reducing agent is selected from one or more of KBH4, NaBH4 and hydrazine hydrate, and the alkaline substance is selected from one or more of sodium hydroxide and potassium hydroxide; preferably, the reducing agent includes NaBH4 and sodium hydroxide; the mass ratio of the iron source to the reducing agent is 1.46-3.65:1, preferably 1.46-2.43:1; in the reducing agent, the molar ratio of the reducing agent to the alkaline substance is 1-20:1, preferably 2.5-13.5:1. The above-mentioned embodiment is conducive to slowing down the self-decomposition of the reducing agent, increasing the concentration of the reducing agent in the reducing agent, and facilitating the formation of crystal nuclei; it is further conducive to obtaining a composite material with a better structure and obtaining a composite material with good dispersibility and stability.

[0048] According to an embodiment of the present disclosure, step (2) includes: mixing the nitrogen-doped graphene, the iron source, and water for a second time to obtain a second mixture; mixing the reducing agent and water for a third time to obtain a reducing solvent; in a further embodiment, mixing the nitrogen-doped graphene and water for a fourth time to obtain a dispersion of nitrogen-doped graphene; mixing the iron source and water for a fifth time to obtain an iron source solution; mixing the iron source solution with the dispersion of the nitrogen-doped graphene to obtain the second mixture; dropping the reducing solvent into the second mixture to carry out the contact reaction; the dropping speed is 0.5 to 1.5 mL / min, preferably 0.7 to 1.2 mL / min; wherein the concentration of the iron source solution is 12 to 112 g / L; and the pH of the reducing solvent is 12.8 to 13.5. The above-mentioned embodiment is conducive to obtaining a composite material with a better structure and obtaining a composite material with good dispersibility and stability.

[0049] According to one embodiment of the present disclosure, in step (2), the cleaning includes using water and ethanol to clean the reaction product. The present disclosure does not impose any specific restrictions on the cleaning method, as long as the cleanliness of the composite material is ensured. For example, ultrapure water can be used for cleaning 3 to 5 times, and then anhydrous ethanol can be used for cleaning 3 to 5 times; the magnetic separation includes separation using a strong rubidium magnet, a ferrite magnet or an electromagnet.

[0050] According to an embodiment of the present disclosure, in step (2), the magnetic separation obtained by the magnetic separation is subjected to the first freeze-drying; the conditions of the first freeze-drying include: a temperature below -50°C, preferably -57 to -73°C, and a time of 15 to 24 hours, preferably 18 to 22 hours. The above embodiment is conducive to maintaining a better structure of the composite material, and further has better dispersibility and stability.

[0051] According to one embodiment of the present disclosure, the graphene oxide is prepared by adopting a modified Hummers method. The modified Hummers method includes acid intercalation oxidation and liquid phase reduction of graphite raw materials to obtain graphene oxide. In one embodiment, the modified Hummers method includes reacting graphite, nitrate, concentrated sulfuric acid and a strong oxidant at a first temperature for 1 to 3 hours; then heating to a second temperature for reaction for 0.2 to 1 hour, cooling to a third temperature and reacting with hydrogen peroxide for 0.5 to 2 hours, and washing the reaction product. The first temperature is -5 to 35°C, the second temperature is 80 to 100°C, and the third temperature is 50 to 70°C.

[0052] According to an embodiment of the present disclosure, before step (1), the graphene oxide is subjected to a second freeze drying. The conditions of the second freeze drying include: a temperature below -50°C, preferably -57 to -73°C, and a time of 24 to 48 hours, preferably 30 to 40 hours. The above embodiment is conducive to the graphene oxide maintaining a good structure and better nitrogen doping and loading of nano iron particles.

[0053] A second aspect of the present disclosure provides a composite material prepared by the method described in the first aspect of the present disclosure.

[0054] The third aspect of the present disclosure provides a composite material of nitrogen-doped graphene loaded with nano-iron rich in pyridinic nitrogen, the composite material comprising nitrogen-doped graphene and nano-iron particles loaded on the nitrogen-doped graphene;

[0055] Based on the total number of atoms of the composite material, the atomic percentage of iron in the composite material is 0.2-70%, preferably 45-55%; the atomic percentage of nitrogen is 0.4-10%, preferably 1-2.5%; wherein the pyridine nitrogen content accounts for 30-60% of the nitrogen content, preferably 40-50%. In the present disclosure, the atomic percentage of iron and the atomic percentage of nitrogen in the composite material are based on the EDS test results of the composite material; the proportion of the pyridine nitrogen content is based on the XPS test results of the composite material.

[0056] According to an embodiment of the present disclosure, the nano iron particle is a core-shell structure and the shell thickness is 1 to 4 nm. The core is a nano iron particle, and the shell is an oxidized shell of the nano iron particle, and the main components of the oxidized shell include iron oxides such as Fe2O3 and Fe3O4. The above embodiment is conducive to improving the ability of the core of the material to transmit electrons outward.

[0057] According to one embodiment of the present disclosure, the BET specific surface area of ​​the nitrogen-doped graphene is 200 to 500 m 2 / g, preferably 230 to 400 m 2 / g; in the composite material, the average particle size of the nano iron particles is 25 to 76 nm, preferably 25 to 58 nm; the average pore size of the composite material is 3.5 to 4.0 nm. In the present disclosure, the average particle size of the nano iron particles is tested by SEM; the average pore size of the composite material is tested by static N2 adsorption-desorption experiment.

[0058] The fourth aspect of the present disclosure provides use of the composite material described in the second aspect or the third aspect of the present disclosure in the remediation of groundwater contaminated by chlorinated hydrocarbons, wherein the mass ratio of the composite material to the chlorinated hydrocarbon is 1 to 5:1, preferably 2 to 4:1.

[0059] The present invention is further described below by way of examples, but the present invention is not limited thereto.

[0060] Unless otherwise specified, the raw materials used in the following examples and comparative examples were commercially available.

[0061] In the present disclosure, the SEM was tested on a ZEISS Gemini 300 instrument, and the EDS was tested on an energy dispersive spectrometer that is equipped with the SEM.

[0062] The transmission electron microscope was tested on a Japanese JEOL JEM-F200 instrument;

[0063] X-ray photoelectron spectroscopy was tested on a Japanese Rigaku R-AXIS RAPID instrument;

[0064] The N2 adsorption / desorption was tested on an ASAP2002 analytical instrument produced by Micromeritics, USA.

[0065] Preparation Example

[0066] Graphene oxide was prepared by the improved Hummers method, including acid intercalation oxidation and liquid phase reduction. Weigh 6g of graphite and 3g of KNO3, add 138mL of 98% concentrated sulfuric acid, and stir evenly in an ice-water bath at 0°C. Then slowly add 9g of KMnO4, continue stirring the reaction in the above ice-water bath for 1 to 2h, and then keep stirring at 35°C for 30min. Add 139mL of deionized water and heat to 98°C, and continue stirring for 30min. Then cool to 60°C, slowly add 15mL of 30% H2O2 and 100mL of deionized water, and stir for 60min. Wash the mixture three times with 1000mL of dilute hydrochloric acid, and then wash the mixture with deionized water until neutral.

[0067] The prepared graphene oxide was freeze-dried and ground, and freeze-dried at -68°C for 40 h to obtain graphene oxide powder GO.

[0068] Example 1

[0069] (1) Weigh 1.2 g of the graphene oxide powder, add 50 mL of ultrapure water and 50 mL of anhydrous ethanol, and ultrasonically disperse for 20 min to form a dispersed graphene oxide suspension, the concentration of the graphene oxide suspension is 12 g / L; weigh 2.4 g of urea and add 50 mL of anhydrous ethanol to fully dissolve; mix the above solutions, and stir magnetically at 40° C. for 8 h until the mixture is sludge-like, to obtain a first mixture, the water content of which is 85%, and the stirring speed is 180 rpm;

[0070] The first mixture obtained in step (1) is transferred to a quartz boat, placed in a quartz tube of a high-temperature tube furnace, nitrogen is introduced, the air in the tube furnace cavity is exhausted, and a temperature control program is set, the heating rate is 10°C / min, and the pyrolysis temperature is 700°C for 3h. During the whole process, nitrogen is introduced as a protective gas, and the flow rate is maintained at 200sccm. After natural furnace cooling, the sample is taken out and ground to obtain a black solid powder, which is nitrogen-doped graphene;

[0071] (2) Weigh 0.25 g of the nitrogen-doped graphene prepared in step (1), disperse it in 100 mL of deoxygenated deionized water by ultrasonication for 20 min until it is uniformly dispersed, and then slowly add 74.4 g / L of FeSO4·7H2O solution under a nitrogen atmosphere, and continue stirring for 30 min to fully mix it to obtain a fourth mixture, wherein the mass ratio of the solute FeSO4·7H2O to the nitrogen-doped graphene is 14.88:1;

[0072] 45 mL of 0.034 g / mL NaBH4 solution and 5 mL of 1 mol / L NaOH solution were mixed evenly, and added dropwise to the second mixture at a dropping speed of 1 mL / min, and stirred continuously for 3 h, wherein the molar ratio of NaBH4 to NaOH was 8:1, the mass ratio of solute FeSO4·7H2O to reducing agent NaBH4 was 2.43:1, and the pH of the reducing solvent was 13; the mixture was washed three times with anhydrous ethanol and deoxygenated deionized water respectively, and then collected with a magnet and freeze-dried at -60 ° C for 32 h to obtain a nitrogen-doped graphene nanoiron composite material, recorded as nZVI3 / N2-rGO 700 .

[0073] The nZVI3 / N2-rGO prepared in this example 700 The scanning electron microscope image of Figure 1 As shown, from Figure 1 It can be seen that the surface of the obtained material is rich in wrinkles, the nano-iron particles are well dispersed, the average particle size of the nano-iron particles is 56.59nm, of which 70% of the nano-iron particles are concentrated in the range of 25 to 76nm, the degree of agglomeration is greatly reduced, and the particle size is relatively uniform.

[0074] The nZVI3 / N2-rGO prepared in this example 700 The transmission electron microscopy image of Figure 2 As shown, it can be seen that the nano-iron particles are mainly distributed in the folds and interlayers of N-rGO, and the particles are surrounded by a thin shell structure with a small thickness of about 2.3nm.

[0075] The nZVI3 / N2-rGO prepared in this example 700 The X-ray photoelectron spectroscopy (XPS) diagram is as follows Figure 3 As shown, specifically N2-rGO 700 (a) and nZVI3 / N2-rGO 700 (b) N1s peak spectrum. The N 1s scanning spectrum can be decomposed into four spectral peaks, namely 397.9eV pyridinic nitrogen (Prd-N), 399.5eV pyrrolic nitrogen (Prl-N), 401eV graphitic nitrogen (Grp-N), and 404.6eV oxidized nitrogen (Oxided-N), among which pyridinic nitrogen accounts for the highest proportion.

[0076] The nZVI3 / N2-rGO prepared in this example 700 The N2 adsorption / desorption isotherms and pore size distribution of the material are shown in Figure 4 As shown, from Figure 4 As can be seen from the figure, nZVI3 / N2-rGO 700 The specific surface area of ​​the material is 41.04m 2 / g, and the average pore size is 3.5-4.0nm.

[0077] The nZVI3 / N2-rGO prepared in this example 700 Thermogravimetric curve of the material is shown in Figure 5 As shown, it can be seen that nZVI3 / N2-rGO 700 The thermal stability is good.

[0078] Example 2

[0079] The method of Example 2 is the same as that of Example 1, except that the pyrolysis temperature in step (1) is 500° C. to obtain a nitrogen-doped graphene nano-iron composite material, denoted as nZVI3 / N2-rGO 500 .

[0080] Example 3

[0081] The method of Example 3 is the same as that of Example 1, except that the pyrolysis temperature in step (1) is 600° C. to obtain a nitrogen-doped graphene nano-iron composite material, denoted as nZVI3 / N2-rGO 600 .

[0082] Example 4

[0083] The method of Example 4 is the same as that of Example 1, except that the pyrolysis temperature in step (1) is 200° C. to obtain a nitrogen-doped graphene nano-iron composite material, denoted as nZVI3 / N2-rGO 200 .

[0084] Example 5

[0085] The method of Example 5 is the same as that of Example 1, except that the dropping speed of the reducing agent in step (1) is 3 mL / min, and a nitrogen-doped graphene nano-iron composite material is obtained, which is recorded as Fe / N2-rGO 700 .

[0086] Example 6

[0087] The method of Example 6 is the same as that of Example 1, except that in step (2), the mass ratio of iron salt to nitrogen-doped graphene is 44.7:1, and a nitrogen-doped graphene nano-iron composite material is obtained, which is recorded as nZVI9 / N2-rGO 700 .

[0088] Example 7

[0089] The method of Example 7 is the same as that of Example 1, except that in step (1), 1.2 g of graphene oxide powder GO is weighed, 6 g of urea is weighed and added, and the mass ratio of the nitrogen source to the graphene oxide is 5:1, thereby obtaining a nitrogen-doped graphene nano-iron composite material, which is recorded as nZVI3 / N5-rGO. 700 .

[0090] Example 8

[0091] The method of Example 8 is the same as that of Example 1, except that in step (2), the mass ratio of the iron salt to the reducing agent sodium borohydride is 3.65:1, and a nitrogen-doped graphene nano-iron composite material is obtained, which is recorded as nZVI-Fe / N2-rGO 700 .

[0092] Comparative Example 1

[0093] 0.25 g of the graphene oxide in the preparation example was weighed, and dispersed in 100 mL of deoxygenated deionized water by ultrasonication for 20 min until it was uniformly dispersed. Then, 74.4 g / L of FeSO4·7H2O solution was slowly added under a nitrogen atmosphere, and stirred for 30 min to fully mix the mixture to obtain a second mixture, wherein the mass ratio of the iron salt to the graphene oxide was 14.88:1;

[0094] 45 mL of 0.034 g / mL NaBH4 solution and 5 mL of 1 mol / L NaOH solution were mixed evenly, and added dropwise to the second mixture at a dropping speed of 1 mL / min, and stirred continuously for 3 h, wherein the molar ratio of NaBH4 to NaOH was 8:1, and the mass ratio of iron salt to reducing agent was 2.43:1; the pH of the reducing solvent was 13; anhydrous ethanol and deoxygenated deionized water were used for washing three times respectively, and then collected by a magnet, and freeze-dried at -68 ° C for 20 h to obtain a composite material of graphene oxide nano-iron, recorded as nZVI3 / GO 700 .

[0095] Test Case

[0096] The atomic percentage of iron, the atomic percentage of nitrogen and the pyridine nitrogen content of the composite materials obtained in Examples 1 to 8 and Comparative Example 1 were tested. At the same time, the specific surface area of ​​the nitrogen-doped graphene / graphene oxide in Examples 1 to 8 and Comparative Example 1 was tested. The results are shown in Table 1.

[0097] Table 1

[0098]

[0099] According to the data in Table 1, the composite material obtained by the method of the present invention has an atomic percentage of iron of 0.2 to 70% and an atomic percentage of nitrogen of 0.4 to 10% based on the total number of atoms of the composite material, and has a rich pyridinic nitrogen content, which accounts for 30 to 60% of the nitrogen content.

[0100] Application Examples

[0101] The composite materials obtained in Examples 1 to 8 and Comparative Example 1 were applied to the removal reaction of tetrachloroethylene. The specific method is: a batch experiment was conducted using a constant temperature oscillating box set at 180 r / min and 25°C as reaction conditions, and a 250 mL blue-capped bottle as a reactor. The initial concentration of tetrachloroethylene was set to 100 mg / L, and an 8-hour reaction experiment was conducted. Samples were taken at intervals, and the concentration of residual tetrachloroethylene was detected using a Shimadzu LC-20A high performance liquid chromatograph. The results are shown in Table 2.

[0102] Table 2

[0103] Composite Materials Removal rate / % Example 1 <![CDATA[nZVI3 / N2-rGO 700 ]]> 95.67 Example 2 <![CDATA[nZVI3 / N2-rGO 500 ]]> 90.07 Example 3 <![CDATA[nZVI3 / N2-rGO 600 ]]> 92.27 Example 4 <![CDATA[nZVI3 / N2-rGO 200 ]]> 64.41 Example 5 <![CDATA[Fe / N2-rGO 700 ]]> 65.94 Example 6 <![CDATA[nZVI9 / N2-rGO 700 ]]> 81.45 Example 7 <![CDATA[nZVI3 / N5-rGO 700 ]]> 74.03 Example 8 <![CDATA[nZVI-Fe / N2-rGO 700 ]]> 62.55 Comparative Example 1 <![CDATA[nZVI3 / GO 700 ]]> 58.60

[0104] According to the data in Table 2, the composite material of pyridinic nitrogen-doped graphene nano-iron rich in the present invention has a good removal effect on tetrachloroethylene. By comparing Examples 1 and 4, it can be seen that within the pyrolysis temperature range of the present invention, the obtained composite material has a better removal effect on tetrachloroethylene. By comparing Examples 1 and 5, it can be seen that within the droplet acceleration range of the reducing agent disclosed in the present invention, the obtained composite material has a better removal effect on tetrachloroethylene. By comparing Examples 1 and 6, it can be seen that within the mass ratio range of the preferred iron source to nitrogen-doped graphene in the present invention, the obtained composite material has a better removal effect on tetrachloroethylene. By comparing Examples 1 and 7, it can be seen that within the mass ratio range of the nitrogen source to the graphene oxide disclosed in the present invention, the obtained composite material has a better removal effect on tetrachloroethylene. By comparing Examples 1 and 8, it can be seen that within the mass ratio range of the preferred iron source to the reducing agent in the present invention, the obtained composite material has a better removal effect on tetrachloroethylene.

[0105] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0106] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0107] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A method for preparing a composite material of nitrogen-doped graphene loaded with nano-iron rich in pyridinic nitrogen, characterized in that: The method comprises the following steps: (1) first mixing graphene oxide, a nitrogen source and a solvent to obtain a first mixture; placing the first mixture in an inert atmosphere for pyrolysis to obtain nitrogen-doped graphene; (2) contacting and reacting the nitrogen-doped graphene, the iron source, the reducing agent and water, and sequentially washing, magnetically separating and freeze-drying the reaction product.

2. The method according to claim 1, wherein: In step (1), the graphene oxide is mixed with the solvent to form a graphene oxide suspension, and then the graphene oxide suspension is mixed with the nitrogen source to obtain the first mixture; The concentration of the graphene oxide suspension is 2 to 20 g / L, preferably 6 to 15 g / L; the solvent includes water and / or ethanol; the nitrogen source is a nitrogen-containing compound selected from one or more of nitrate, ammonia water, urea, biomass and hydrazine hydrate; preferably one or more of urea, ammonia water and hydrazine hydrate; more preferably urea; The mass ratio of the nitrogen source to the graphene oxide is 1 to 3:

1.

3. The method according to claim 1, wherein: In step (1), the pyrolysis conditions include: a heating rate of 5 to 15°C / min, a pyrolysis temperature of 300 to 900°C, and a pyrolysis time of 1 to 5 hours; preferably, a heating rate of 7 to 12°C / min, a pyrolysis temperature of 500 to 700°C, and a pyrolysis time of 2 to 4 hours.

4. The method according to claim 1, wherein: In step (1), the conditions of the first mixing include: the first mixing is carried out under stirring, the stirring speed is 110 to 260 rpm, preferably 180 to 210 rpm; the temperature of the first mixing is below 40° C., preferably 20 to 40° C.; the time of the first mixing is 4 to 20 hours, preferably 6 to 10 hours; the first mixture is in a sludge-like state, and the water content is 70% to 98%.

5. The method according to claim 1, wherein: In step (2), the iron source is a ferric salt and / or a ferrous salt; the iron source is selected from one or more of FeCl3, FeCl2 and FeSO4·7H2O; preferably a ferrous salt, more preferably FeSO4·7H2O; The mass ratio of the iron source to the nitrogen-doped graphene is 4.9 to 44.7:1, preferably 4.9 to 14.9:1; The reducing agent comprises a reducing agent and an alkaline substance, the reducing agent is selected from one or more of KBH4, NaBH4 and hydrazine hydrate, and the alkaline substance is selected from one or more of sodium hydroxide and potassium hydroxide; preferably, the reducing agent comprises NaBH4 and sodium hydroxide; The mass ratio of the iron source to the reducing agent is 1.46-3.65:1, preferably 1.46-2.43:1; in the reducing agent, the molar ratio of the reducing agent to the alkaline substance is 1-20:1, preferably 2.5-13.5:

1.

6. The method according to claim 1, wherein: Step (2) comprises: performing a second mixing of the nitrogen-doped graphene, the iron source and water to obtain a second mixture; performing a third mixing of the reducing agent and water to obtain a reducing solvent; dropping the reducing solvent into the second mixture to carry out the contact reaction; the dropping speed is 0.5 to 1.5 mL / min, preferably 0.7 to 1.2 mL / min; the pH of the reducing solvent is 12.8 to 13.

5.

7. The method according to claim 1, wherein: In step (2), the magnetic separation product obtained by the magnetic separation is subjected to the first freeze-drying; the conditions of the first freeze-drying include: a temperature below -50°C, preferably -57 to -73°C, and a time of 15 to 24 hours, preferably 18 to 22 hours.

8. The method according to claim 1, wherein: The graphene oxide is prepared by adopting an improved Hummers method.

9. The composite material prepared by the method according to any one of claims 1 to 8.

10. A composite material of nitrogen-doped graphene loaded with nano-iron rich in pyridinic nitrogen, characterized in that: The composite material includes nitrogen-doped graphene and nano-iron particles supported on the nitrogen-doped graphene; Based on the total number of atoms of the composite material, the atomic percentage of iron in the composite material is 0.2-70%, and the atomic percentage of nitrogen is 0.4-10%, wherein the pyridine nitrogen content accounts for 30-60% of the nitrogen content.

11. The composite material according to claim 10, wherein The nano iron particles are of a core-shell structure and the shell thickness is 1-4 nm.

12. The composite material according to claim 10, wherein The BET specific surface area of ​​the nitrogen-doped graphene is 200 to 500 m 2 / g; the average particle size of the nano iron particles is 50-60nm; the average pore size of the composite material is 3.5-4.0nm.

13. Use of the composite material according to any one of claims 9 to 12 in the remediation of groundwater contaminated by chlorinated hydrocarbons, characterized in that: The mass ratio of the composite material to the chlorinated hydrocarbon is 1 to 5:1.

Citation Information

Patent Citations

  • Magnetic nitrogen-doped reduced graphene oxide compound catalyst as well as preparation method and application thereof

    CN107020144A

  • Nitrogen-doped graphene supported iron-based catalyst as well as preparation method and application thereof

    CN108273504A

  • Three-dimensional graphene macroscopic body loaded nanoscale zero-valent iron composite material and preparation method thereof

    CN109173989A

  • Preparation method and application of nitrogen-doped three-dimensional graphene aerogel loaded nano zero-valent iron

    CN111939960A